Vietnam and Threshold Conditions in the Process of Global Financial Integration - Nguyen, Thi Ngoc Trang (University of Economics Ho Chi Minh City, 2023)
The global financial crisis, once again, has ignited several intense debates over financial globalization merits, particularly for developing countries. There are probably a number of initial threshold conditions to be attained before substantial benefits may be reaped, and the risks of capital account liberalization, minimized. This article takes into account a series of empirical framework typifying these threshold conditions, estimating essential ones and accordingly proposing a few policy implications. Empirical evidence demonstrates that there exist specific thresholds in such variables with significant effects on the nexus between financial integration and growth, including those as clearly identifiable as financial depth and institutional quality. It is also shown by the findings that Vietnam’s financial development has preliminarily satisfied the necessary conditions for efficient financial integration. In contrast, the institutional quality threshold remains far distant.